Penerapan Model Pembelajaran Kontekstual Dalam Meningkatkan Hasil Belajar IPA Siswa Kelas IV - Rosmalah Rosmalah; Muhammad Idris Djafar; Nur afia amali (Universtas Negeri Makassar, 2023)
Abstract. This research is classroom action research (CAR). The approach used is descriptive qualitative. The focus of this research is 1) Application of contextual learning model, 2) Student learning outcomes. The research subjects were fourth grade students at SDN 209 Kajaolaliddong. The objectives of this study: 1) determine the application of contextual learning models in improving science learning outcomes for fourth grade students. 2) knowing the results of applying contextual learning models in improving science learning outcomes for fourth grade students. The subjects of this study were students with a total of 17 people consisting of 9 males and 8 females. Data collection techniques used were observation and tests. Data analysis techniques of this study were data reduction, data presentation and drawing conclusions. The results of the study showed an increase. Cycle I achieved the qualification of Good (B) and in the second cycle achieved the qualification of Very Good (A). The conclusion of this study is that applying a contextual learning model can improve science learning outcomes for fourth grade students at SDN 209 Kajaolaliddong, Barebbo District, Bone Regency.Keywords: Contextual learning, Learning outcomes, ScienceAbstrak: Penelitian ini adalah penelitian tindakan kelas (PTK). Pendekatan yang di gunakan dalam penelitian ini adalah kualitatif bersifat deskripstif. Fokus dalam penelitian ini adalah 1) penerapan model pembelajaran kontekstual, 2) Hasil belajar siswa. Subjek dalam penelitian adalah siswa kelas IV SDN 209 Kajaolaliddong Kecamatan Barebbo Kabupaten Bone. Tujuan penelitian ini yaitu untuk: 1) mengetahui penerapan model pembelajaran kontekstual dalam meningkatkan hasil belajar IPA siswa kelas IV SDN 209 Kajaolaliddong Kecamatan Barebbo Kabupaten Bone. 2) mengetahui hasil penerapan model pembelajaran kontekstual dalam meningkatkan hasil belajar IPA siswa kelas IVSDN 210 Kajaolaliddong Kecamatan Barebbo Kabupaten Bone. Subjek dalam penelitian ini adalah siswa dengan jumlah 17 orang yang terdiri dari 9 laki-laki dan 8 perempuan. Teknik pengumpulan data yang digunakan adalah observasi dan tes. Teknik analisis data dalam penelitian ini adalah reduksi data, penyajian data dan menarik kesimpulan. Hasil penelitian menujukkan adanya peningkatan. Siklus I mencapai kualifikasi Baik (B) dan pada siklus II mencapai kualifikasi Sangat Baik (A). Kesimpulan dalam penelitian ini adalah dengan menerapkan model pembelajaran kontekstual dapat meningkatkan hasil belajar IPA siswa kelas IV SDN 209 Kajaolaliddong Kecamatan Barebbo Kabupaten Bone.Kata Kunci : Pembelajaran kontektual, Hasil belajar, IPA